Functionalized Sawdust-Derived Cellulose Nanocrystalline Adsorbent for Efficient Removal of Vanadium From Aqueous Solution - Zulu, Bongiwe; Oyewo, Opeyemi A.; Sithole, Bruce; Leswifi, Taile Y.; Onyango, Maurice S. (Frontiers in Environmental Science, 2020)
Water quality degradation due to noxious heavy metals has become a serious concern because of its impact on human health and the ecosystem. In this study, cellulose nanocrystal (CNC) derived from sawdust as a green renewable and sustainable resource was functionalized and used as adsorption media to remove pentavalent vanadium (V) from aqueous solution. The physicochemical properties of the adsorbent were studied using various characterization techniques such as Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and X-ray diffraction (XRD). The performance of the functionalized CNC adsorbent was explored as a function of solution pH, temperature, adsorbent mass, time, and initial concentration in batch adsorption. XRD results confirmed the crystalline nature of the CNC, which was more pronounced upon modification. The SEM micrograph revealed rough surface and high porosity, which suggested that the CNC possessed prerequisite properties of a good adsorbent. From the FTIR spectra results, the interaction between anionic vanadium species and functionalized CNC was confirmed by the reduction in wavelength of carboxylic groups (–COOH) of the CNC. Meanwhile, from the adsorption results, V removal efficiency was found to be affected by solution pH, temperature, adsorbent mass, and initial concentration. The Langmuir maximum adsorption capacity was 37.9–47.2 mg/g in the temperature range studied. In evaluating the reusability of the CNC through adsorption–desorption studies, results confirmed that the functionalized CNC could be used more than once with about 20% reduction in adsorption of V in each adsorption–desorption cycle. So far, there are indications that modified CNC may be an alternative adsorption media for V.